PENGARUH PENGHARGAAN FINANSIAL DAN PERTIMBANGAN PASAR KERJA TERHADAP MINAT MENJADI AKUNTAN PUBLIK - Kurniawan , Kurniawan; Kasmawati, Kasmawati; Nugraha JS, Romy (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to determine the extent to which Financial Rewards (X1) and Job Market Considerations (X2) influence the Interest in Becoming a Public Accountant among students of the Accounting Study Program at Universitas Ichsan Sidenreng Rappang. The research employs a descriptive quantitative approach with an associative research type. The population consists of all students in the Accounting Study Program, with a sample drawn from the 2022 and 2023 student cohorts. The sampling technique used is purposive sampling and judgment sampling. Research instruments were tested using validity and reliability tests, along with normality testing and conversion of data from ordinal to interval scale before analysis. The data analysis technique used is path analysis, which aims to identify causal relationships between variables. The results show that Financial Rewards and Job Market Considerations simultaneously contribute 0.612 or 61.2% to the students’ interest in becoming public accountants. The remaining 38.8% is influenced by other variables not examined in this study. Hypothesis testing also indicates that, both partially and simultaneously, Financial Rewards and Job Market Considerations have a positive and significant influence on the Interest in Becoming a Public Accountant. Specifically, the Financial Rewards variable contributes 14.4%, while the Job Market Considerations variable contributes 46.8% to the interest in pursuing this career.